2003
DOI: 10.1590/s1415-47572003000200008
|View full text |Cite
|
Sign up to set email alerts
|

Genetic differentiation of Macrodon ancylodon (Sciaenidae, Perciformes) populations in Atlantic coastal waters of South America as revealed by mtDNA analysis

Abstract: The king weakfish (pescada-gó in Portuguese -Macrodon ancylodon (Sciaenidae), a demersal (bottom-feeding) species found in South America Atlantic coastal waters from the Gulf of Paria in Venezuela to Baia Blanca in Argentina, is an economically important species because of its abundance and wide acceptance by consumers. Because of its wide distribution this fish may be subject to geographic isolation and this may have resulted in distinct populations along its coastal range. Considering that this species repre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
45
1
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 44 publications
4
45
1
2
Order By: Relevance
“…Our result was different to Santos et al (2003) study which found high genetic distances in cyt b gene of geographically separated Macrodon ancylodon populations and Craig et al (2009) which also observed a high genetic difference among goliath grouper (Epinephelus itajara) populations. The differences between our result and the study from Santos et al (2003) and Craig et al (2009) might due to we used a different source of populations. In one hand, we used cultivated populations which might be under similar selecti-on pressure from breeder to develop high-quality strains.…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…Our result was different to Santos et al (2003) study which found high genetic distances in cyt b gene of geographically separated Macrodon ancylodon populations and Craig et al (2009) which also observed a high genetic difference among goliath grouper (Epinephelus itajara) populations. The differences between our result and the study from Santos et al (2003) and Craig et al (2009) might due to we used a different source of populations. In one hand, we used cultivated populations which might be under similar selecti-on pressure from breeder to develop high-quality strains.…”
Section: Resultscontrasting
confidence: 99%
“…The fragment of cytochrome b gene was multiplied utilizing a pair of primer as follows; forwards L14725L:5'CGA AAC TAA TGA CTT GAA AAA CCA CCG TTG3' and reverse HMVZ16:5'AAA TAG GAA RTA TCA YTC TGG TTT RAT3' (Santos et al, 2003). A total volume of 50 µl of PCR reactions was used during amplification.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These species include Pristipomoides multidens (Ovenden et al 2004), Lutjanus erythropterus (Zhang et al 2006), and L. synagris (Karlsson et al 2009). Other perciforms, such as the king weakfish, Macrodon ancylodon, also present considerable genetic differentiation at the population level (Santos et al 2003(Santos et al , 2006. These authors recorded the presence of two distinct genetic stocks of M. ancylodon along the Atlantic coast of South America, which they interpreted as the result of a process of allopatric differentiation.…”
Section: Discussion Brazilian L Purpureus Phylogeography and Populatmentioning
confidence: 99%
“…2,400 km of coastline as the one inhabited by the studied Brazilian populations of Ocyurus chrysurus. Differences in oceanographic conditions, mainly sea-water temperature, were reported to this area (Castro and Miranda, 1998) being regarded as an important factor in the genetic differentiation of Macrodon ancylodon populations along the Brazilian coast (Santos et al, 2003). Cases where morphometric and genetic data indicate different scenarios of population structuring are not uncommon (Salini et al, 2004;Levi et al, 2004).…”
mentioning
confidence: 89%